'But the real problem is….': The Chameleonic Insidiousness of 'Overpopulation' in the Environmental Humanities. Issue 1 (July 2016) - Clark, Timothy
Abstract : This paper offers an overview of the chameleonic nature of overpopulation as an environmental issue, and of the relative evasion of population as an issue in ecocriticism and elsewhere: the very multiplicity of environmental factors means that population pressure can always seem to be finessed as "really" something else. Overpopulation looks drastically different as an issue, depending on whether it is considered at the level of the nation state, that of individual right, or as a global phenomenon. Finally, the chameleonic nature of overpopulation poses intractable challenges to literary representation, since it resists representation at the scalar norms of realism.